Follow-ups in the US anti-terrorist discourse: Proposal for a macro-discursive approach to monologic follow-up sequences. (September 2015) - Cap, Piotr
Follow-ups have been routinely considered a dialogic/conversational phenomenon. In this article, I demonstrate that the concept of follow-up could be extended to cover monologic discourses as well, especially those in which the speaker realizes a macro-goal over a number of texts produced in different contextual conditions. These dynamically evolving conditions make the speaker – as happens in dialogue – continually update and redefine his or her rhetorical choices to maintain realization of the macro-goal intact. Such an approach subsumes a 'dialogic' relation between the speaker and the shifting discourse context – rather than between the speaker and his or her specific interlocutor – and views follow-up as an instance of rhetoric that has been forcibly modified from the previous/initial instance, to keep enacting the speaker's macro-goal against requirements of the new context. As an illustration, I show how monologic follow-ups work in George W. Bush's War-on-Terror discourse. In particular, I discuss how the macro-goal of Bush's 2003–2004 rhetoric of the Iraq War (legitimization of the pre-emptive military strike and the later US involvement) has been maintained in the 'follow-up speeches' responding to loss of the initial legitimization premise, that is, the alleged possession of weapons of mass destruction by the Iraqi dictator Saddam Hussein.